2010
DOI: 10.1007/s11096-010-9393-x
|View full text |Cite
|
Sign up to set email alerts
|

Provision of pharmaceutical care by community pharmacists: a comparison across Europe

Abstract: The present findings suggest that the provision of pharmaceutical care in community pharmacy is still limited within Europe. Pharmacists were routinely engaged in general activities such as patient record screening but were infrequently involved in patient centred professional activities such as the implementation of therapeutic objectives and monitoring plans, or in self-evaluation of performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 17 publications
10
80
0
2
Order By: Relevance
“…Although there are several definitions of this concept, most agree that a pharmacist's commitment to the patient is to attain the patient's health objectives. This concept has become widely used in North America, particularly in Quebec, but it has received less recognition in Europe [10], with the exception of the United Kingdom and the Netherlands [8]. The pharmacists' practices considered in the present study are integrated into the concept of pharmaceutical care that is defined by the Ordre des Pharmaciens du Québec (The College of Pharmacists in Quebec) as: "all the acts and services that the pharmacist is required to provide to patients, in order to improve the quality of their lives by attaining the pharmacotherapeutic objectives of prevention, cure or the provision of palliative care."…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several definitions of this concept, most agree that a pharmacist's commitment to the patient is to attain the patient's health objectives. This concept has become widely used in North America, particularly in Quebec, but it has received less recognition in Europe [10], with the exception of the United Kingdom and the Netherlands [8]. The pharmacists' practices considered in the present study are integrated into the concept of pharmaceutical care that is defined by the Ordre des Pharmaciens du Québec (The College of Pharmacists in Quebec) as: "all the acts and services that the pharmacist is required to provide to patients, in order to improve the quality of their lives by attaining the pharmacotherapeutic objectives of prevention, cure or the provision of palliative care."…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as the study was to be undertaken over a very short period of time (1 month), one could not expect a high participation rate neither a high recruitment rate from each of the participating pharmacies. The pharmacy participation rate was assumed to be 15 % based on previous studies [30,31], indicating 99 pharmacies would participate. As such, to achieve the estimated sample size each pharmacy would have to recruit 3.78 patients.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Urban and colleagues found that the potential of community pharmacists to improve patient safety after discharge from hospital is not being used in England [9]. Across Europe pharmacists are infrequently involved in patient-centred professional activities such as monitoring plans [10]. The situation in the US differs to some extent as the implementation of collaborative working relationships between community pharmacists and physicians aims at fostering interprofessional collaboration.…”
Section: Introductionmentioning
confidence: 99%